The Effect of Blood Flow-Restricted Low Resistance Training on Microvascular Circulation of Myocardium in Spontaneously Hypertensive Rats - Tan, Zhaowen; Zhao, Yan; Zheng, Yuchan; Pan, Ying (Frontiers in Physiology, 2022)
Objective: The purpose of this study was to explore the effect of blood flow-restricted low resistance training on microvascular rarefaction in the myocardium of spontaneously hypertensive rats (SHRs). Methods: Four-week-old male SHRs were randomly divided into the following groups: Wistar-Kyoto (WKY), SHR control (SHR-SED), high-intensity resistance training (HIRT), low-intensity resistance training (LIRT), and blood flow-restricted low resistance training (BFRT). The exercise groups began to receive exercise intervention for 8 weeks at the age of 7 weeks. Blood pressure (BP), heart rate (HR), cardiac function, capillary density, and Vascular endothelial growth factor -Phosphatidylinositol 3-kinase-Protein kinase B-Endothelial nitric oxide synthetase (VEGF-Pi3k-Akt-eNOS) were assessed. Results: 1) BP and HR of BFRT decreased significantly, Ejection fraction (EF) and Fraction shortening (FS) increased, and the effect of BFRT on lowering BP and HR was better than that of other groups (P < 0.05); 2) The expression of VEGF, VEGFR2, p-VEGFR2, Pi3k, Akt, p-Akt, eNOS and p-eNOS in the myocardium of the BFRT was significantly upregulated, and eNOS expression was significantly higher than other groups (P < 0 05); 3) the expression of VEGF in the blood of the BFRT was significantly upregulated, higher than SHR-SED, lower than HIRT (P < 0.05), and there was no significant difference between BFRT and LIRT(P > 0.05); 4) the capillary density in the myocardium of BFRT was significantly higher than other exercise groups (P < 0 05). Conclusion: Blood flow-restricted low resistance training can activate the VEGF-Pi3k-Akt-eNOS pathway, upregulate the expression of VEGF in blood, improve microvascular rarefaction, and promote myocardial microvascular circulation, thereby improving cardiac function and lowering blood pressure, achieving the preventive effect of early hypertension.